Advertising agency selection, customer retention and satisfaction factors: an exploratory research in the Greek advertising market. (11th September 2019) - Katsonis, Nikolaos; Tsekouropoulos, Georgios; Theocharis, Dimitrios; Katavelos, Antonios
Customer retention and long-term relationships can result on multiple benefits for an agency. On the other hand, relationship termination can be very costly for clients and agencies. Advertisers' decision regarding the selection of an advertising agency is influenced by a number of factors. For these reasons, a primary research was conducted in order to investigate from the side of the advertisers, the selection and retention criteria, as well as the importance of specific attributes for the satisfaction from an advertising agency and its evaluation. Among others the findings of the primary research indicate that creativity; quality of service; price and professional and technical skills are the most important factors for agency selection, satisfaction with the level of service; quality of client care; professional and technical skills and creativity are the most important factors for agency retention.